2019
DOI: 10.1371/journal.pone.0218594
|View full text |Cite
|
Sign up to set email alerts
|

A method to concatenate multiple short time series for evaluating dynamic behaviour during walking

Abstract: Gait variability is a sensitive metric for assessing functional deficits in individuals with mobility impairments. To correctly represent the temporal evolution of gait kinematics, nonlinear measures require extended and uninterrupted time series. In this study, we present and validate a novel algorithm for concatenating multiple time-series in order to allow the nonlinear analysis of gait data from standard and unrestricted overground walking protocols. The full-body gait patterns of twenty healthy subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…The ability to walk longer distances is instrumental for humans to perform various activities of daily living and lead an independent life. Walking requires complex mechanisms within the human sensory motor system to provide the necessary timing, coordination, and balance such that the interplay between the center of mass and the base of support are regulated in a repetitive manner (46,56).…”
Section: Purposeful Continuous Walksmentioning
confidence: 99%
“…The ability to walk longer distances is instrumental for humans to perform various activities of daily living and lead an independent life. Walking requires complex mechanisms within the human sensory motor system to provide the necessary timing, coordination, and balance such that the interplay between the center of mass and the base of support are regulated in a repetitive manner (46,56).…”
Section: Purposeful Continuous Walksmentioning
confidence: 99%
“…Further, within in-lab settings, it has been demonstrated that gait irregularity can differ between non-frail and pre-frail older adults (21). We used Sample Entropy (SampEn) assessment defined as equation (2), where was defined as the number of matches in the filtered acceleration signal length (distance function smaller than tolerance ) and as the number of matches of length ( ) (50)(51)(52)(53)(54).…”
Section: Continuous Walking Boutsmentioning
confidence: 99%
“…The ability to walk longer distances is instrumental for humans to perform various activities of daily living and lead an independent life. Walking requires complex mechanisms within the human sensory motor system to provide the necessary timing, coordination, and balance such that the interplay between the center of mass and the base of support are regulated in a repetitive manner (51,61).…”
Section: Continuous Walksmentioning
confidence: 99%
“…The ability to walk longer distances is instrumental for humans to perform various activities of daily living and lead an independent life. Walking requires complex mechanisms within the human sensory motor system to provide the necessary timing, coordination, and balance such that the interplay between the center of mass and the base of support are regulated in a repetitive manner (54,64). Previous studies that explored the gait characteristics of non-disabled adults for two weeks to define walking duration, found that 81% of all walking bouts lasted about 60 seconds (35,36).…”
Section: Continuous Walksmentioning
confidence: 99%